Estudio jurídico y doctrinario de las tendencias anunciadas por la Corte Constitucional en la sentencia Nro. 200-12-JH/21 para garantizar el interés superior de niños, niñas y adolescentes - Pardo Luna, Angie Alexandra (2023)
The following research work "Legal and doctrinal study of the trends announced by the Constitutional Court in Ruling No. 200-12-JH/21 to guarantee the best interests of children and adolescents". This study examines the legal and doctrinal aspects of the tendencies that were announced in sentence No. 200-12-JH/21 to guarantee the best interests of children and adolescents, which is a research project based on the dissolution of a marriage or a de facto bond, when it is evident that children are involved. Due to the fact that one parent has custody of the child, conflicting situations exist between parents for a variety of reasons. This prevents the implementation of the visitation regime, which is essential for the development of children and adolescents on an integral basis and in their best interests. The analyzed judgment deals with the habeas corpus actions filed for personal coercion that were exercised in the two judicial proceedings analyzed, based on code 125 of the Organic Code of Childhood and Adolescence. The Constitutional Court identified the origin of habeas corpus in this type of proceeding, established parameters to prevent deprivation of liberty from becoming arbitrary and/or illegal, and elaborated general trends to evaluate the needs and interests of children and adolescents. As a result of the application of materials and methods, the research was able to be developed; in addition, interviews and surveys with legal professionals with an emphasis on Family Law were conducted, resulting in conclusions and recommendations aimed at safeguarding children's and adolescents' best interests.